Factors Affecting Therapeutic Compliance among the Patients with Rheumatic Heart Disease in Bangladesh (Cardiovascular Journal, 2018)
Background: Acute rheumatic fever (ARF) can recur as a result of subsequent Group A Streptococcus (GAS) infections and each recurrence can worsen Rheumatic heart disease (RHD) that has evoked a substantial disease burden in developing countries, including Bangladesh. The objective of this study was to determine the penicillin compliance for rheumatic fever patients.Methods: A matched cross sectional study was conducted among 160 patients in National Center for the Control of Rheumatic Fever and Heart Diseases (NCCRF/HD), Dhaka. Data was collected on face-to-face interview using a standard structured questionnaire about socio-demographic, clinical and behavioral factors. Descriptive and multivariate logistic regression analyses were used to analyze the data.Results: The multiple logistic regression analyses indicated that duration of diagnosis>5 beyond the duration of diagnosis